Involvement of three chemosensory proteins in perception of host plant volatiles in the tea green leafhopper, Empoasca onukii - Zhang, Liwen; Zhao, Mingxian; Aikeremu, Feiruoran; Huang, Huoshui; You, Minsheng; Zhao, Qian (Frontiers in Physiology, 2023)
Chemosensory proteins (CSPs) can bind and transport odorant molecules, which are believed to be involved in insect chemoreception. Here, we investigated three CSPs in perception of volatiles in Empoasca onukii. Expression profiles showed that although EonuCSP4, EonuCSP 6-1 and EonuCSP6-2 were ubiquitously expressed in heads, legs, thoraxes and abdomen, they were all highly expressed in the antennae of E. onukii. Further, fluorescence competitive binding assays revealed that EonuCSP4 and 6-1 had binding affinities for three plant volatiles, suggesting their possible involvement in the chemosensory process. Among them, EonuCSP6-1 showed relatively high binding affinities for benzaldehyde. Behavioral assays revealed that the adults of E. onukii showed a significant preference for two compounds including benzaldehyde. The predicted three-dimensional (3D) structures of these 3 CSP have the typical six α-helices, which form the hydrophobic ligand-binding pocket. We therefore suggest that Eoun6-1 might be involved in the chemoreception of the host-related volatiles for E. onukii. Our data may provide a chance of finding a suitable antagonist of alternative control strategies which block the perception of chemosensory signals in pest, preventing the food- orientation behaviors.